Single-Site Cannulation Venovenous Extracorporeal CO2 Removal as Bridge to Lung Volume Reduction Surgery in End-Stage Lung Emphysema. Issue 6 (November 2016) - Redwan, Bassam; Ziegeler, Stephan; Semik, Michael; Fichter, Joachim; Dickgreber, Nicolas; Vieth, Volker; Ernst, Erik Christian; Fischer, Stefan
Abstract : Lung volume reduction surgery (LVRS) is an important treatment option for end-stage lung emphysema in carefully selected patients. Here, we first describe the application of low-flow venovenous extracorporeal CO2 removal (LFVV-ECCO2R) as bridge to LVRS in patients with end-stage lung emphysema experiencing severe hypercapnia caused by acute failure of the breathing pump. Between March and October 2015, n = 4 patients received single-site LFVV-ECCO2R as bridge to LVRS. Indication for extracorporeal lung support was severe hypercapnia with respiratory acidosis and acute breathing pump failure. Two patients required continuous mechanical ventilation over a temporary tracheostomy and were bed ridden. The other two patients were nearly immobile because of severe dyspnea at rest. Length of preoperative ECCO2R was 14 (1–42) days. All patients underwent unilateral LVRS. Anatomical resection of the right (n = 3) or left (n = 1) upper lobe was performed. Postoperatively, both patients with previous mechanical ventilatory support were successfully weaned. ECCO2R in patients with end-stage lung emphysema experiencing severe hypercapnia caused by acute breathing pump failure is a safe and effective bridging tool to LVRS. In such patients, radical surgery leads to a significant improvement of the performance status and furthermore facilitates respiratory weaning from mechanical ventilation.